(untitled) (Research, Society and Development, 2020)
Parkinson’s disease is a cognitive and degenerative condition that affects mostly elderly people, altering and compromising the affected person’s entire motor life, as well as their independence. Some of the most well-known symptoms are tremors and muscle stiffness, a consequence of this, social discomfort and lack of human contact take center stage, as the embarrassment of attending public events and getting dirty during eating becomes a reality, generating depression and anxiety disorders. That said, this article aims to suggest a clothing product proposal, where it is possible to align fashion information, increasing its aesthetic-symbolic function, covering the visual aspects considered as elegant and beautiful from the target audience worked, with the specific practical function, increasing users’ self-esteem, providing a better quality of life to women with Parkinson’s in the elderly, focusing on their social scope. This project was carried out through a literature search with an exploratory approach, combined with the product development methodologies of Mike Baxter and Bernd Lobach. As a general result, a coat in a social style was obtained as a product that managed to balance aesthetic appeal with the practicality conferred through fabric with impermeable characteristics.